2013
DOI: 10.1111/tme.12057
|View full text |Cite
|
Sign up to set email alerts
|

The epidemiology of human T‐cell lymphotropic virus types I and II in Canadian blood donors

Abstract: With testing of the blood supply, the risk from HTLV is very low and while most HTLV-positive donors have risk factors, deferrable risk is rare.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 27 publications
0
21
0
Order By: Relevance
“…29,30 HBV and HTLV infections are strongly associated with country of birth. 16,19,[31][32][33] In Dutch new donors, the majority of HBV and HTLV infections was linked to firstgeneration migrants from Asia (in particular Turkey) and Latin America (Surinam plus the Dutch Caribbean), respectively. In contrast, acute HBV and HTLV infections almost exclusively occurred in "indigenous" Dutch donors.…”
Section: Discussionmentioning
confidence: 99%
“…29,30 HBV and HTLV infections are strongly associated with country of birth. 16,19,[31][32][33] In Dutch new donors, the majority of HBV and HTLV infections was linked to firstgeneration migrants from Asia (in particular Turkey) and Latin America (Surinam plus the Dutch Caribbean), respectively. In contrast, acute HBV and HTLV infections almost exclusively occurred in "indigenous" Dutch donors.…”
Section: Discussionmentioning
confidence: 99%
“…Although not a formal retrospective study, a look back study by Kleinman et al in the same era showed that 16 of 54 (30%) evaluable recipients of blood products from HTLV-1 or HTLV-2 infected donors themselves became infected [6]. In a Canadian lookback study, of 109 HTLV-positive donors, 508 components were transfused, of whom 147 recipients were tested and 18 (12%) were positive [7]. …”
Section: Early Epidemiologic Studies Of Transfusion Transmissionmentioning
confidence: 99%
“…In Canada, there was only one incident case of HTLV infection from 2007–2010 for an estimated incidence of 0.09 per 10 5 and a residual risk of 0.13 per 10 6 [7]. Similarly, incidence has been estimated to be 3.59 per 10 5 in Brazil from 2007–2009 with residual transfusion risk of 5.0 per 10 6 per blood products transfused [19].…”
Section: Htlv-1 and -2 Incidence And Residual Riskmentioning
confidence: 99%
“…HTLV‐II appears to be more associated with the Americas, particularly indigenous peoples and intravenous drug users. The HTLV rate in Canadian blood donors is about 1 per 100 000 donations of which about one quarter are HTLV‐II . This trend has not changed in more than 20 years of monitoring.…”
Section: Introductionmentioning
confidence: 99%
“…This trend has not changed in more than 20 years of monitoring. The main risk factors in donors with HTLV‐I are history of other sexually transmitted diseases and being born outside Canada/USA, while HTLV‐II‐positive donors are generally born in Canada and tend to have sexual risk factors . Importantly, most HTLV‐positive donations are from first‐time donors and are very rare among repeat donors.…”
Section: Introductionmentioning
confidence: 99%